Towards Local Community Involvement in Students’ Science Learning: Perspectives of Students and Teachers - Suero Montero, Calkin; Oliveira Leite, Lais (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2022)
The European Commission calls for schools to move towards becoming open to their communities, integrating external social, civil, and expert stakeholders into authentic learning experiences’ development alongside teachers and students, particularly in terms of science education. However, little research or practical implementation has been reported on how community actors could participate in the development of such curricular learning activities. In this study, we present an implementation of the open science schooling (OSS) approach to science learning, where community involvement in the development of science missions takes a vital role. During the study, students developed science missions related to local societal issues that interested them in collaboration with their teachers and community experts, with frequent hands-on investigations outside their classrooms or laboratories, in five European countries and Israel. Questionnaires with quantitative and qualitative questions concerning students’ and teachers’ views and perspectives about implementing science education using OSS were administered after the participants finished their science missions. The results indicate the effectiveness of the OSS approach to science learning involving the community from both students’ and teachers’ perspectives. This study is a step towards supporting schools in becoming active agents of change through the implementation of contextualized learning experiences alongside external stakeholders.